Answer:
[1, 1]
Step-by-step explanation:
Translation → [-1, 3] moves down to [-1, 1]
Now, a <em>90°-clockwise rotation</em> is the exact same as a <em>270°-counterclockwise rotation</em>, and according to the <em>270°-counterclockwise rotation</em> [<em>90°-clockwise rotation</em>] rule, you take the y-coordinate, bring it over to your new x-coordinate, and take the OPPOSITE of the x-coordinate and set it as your new y-coordinate:
<u>Extended Rotation Rules</u>
- 270°-clockwise rotation [90°-counterclockwise rotation] >> (<em>x, y</em>) → (<em>-y, x</em>)
- 270°-counterclockwise rotation [90°-clockwise rotation] >> (<em>x, y</em>) → (<em>y, -x</em>)
- 180°-rotation >> (<em>x, y</em>) → (<em>-x, -y</em>)
Then, you perform your rotation:
270°-counterclockwise rotation [90°-clockwise rotation] → [-1, 1] moves to [1, 1]
I am joyous to assist you anytime.